Funnel control of linear systems under output measurement losses - Lanza, Lukas Johannes; Berger, Thomas

Network and Service Coordination: Conventional and Machine Learning Approaches" - Schneider, Stefan Balthasar

A Reference Process Model for Usage Data-Driven Product Planning - Meyer, Maurice; Wiederkehr, Ingrid; Panzner, Melina; Koldewey, Christian; Dumitrescu, Roman (Proceedings of the 55th Hawaii International Conference on System Sciences)
Cyber-physical systems generate and collect huge amounts of usage data during operation. Analyzing these data may enable manufacturing companies to identify weaknesses and learn about the users of their products. Such insights are valuable in the early phases of product development like product planning, as they facilitate decision-making for product improvement. The analysis and exploitation of usage data in product planning, however, is a new task for manufacturing companies. To reduce mistakes and improve the results, companies should build upon a suitable reference process model. Unfortunately, established models for analyzing data cannot be easily applied for product planning. In this paper, we propose a reference process model for usage data-driven product planning. It builds on three well-established models for analyzing data and addresses the unique characteristics of usage data-driven product planning. Finally, we customize the model for a manufacturing company and demonstrate how it could be implemented in practice.

Enhancing Human-in-the-Loop Adaptive Systems through Digital Twins and VR Interfaces - Yigitbas, Enes; Karakaya, Kadiray; Jovanovikj, Ivan; Engels, Gregor (Software Engineering 2022, Fachtagung des GI-Fachbereichs Softwaretechnik, 21.-25. Februar 2022, Virtuell)

Collaborative Software Modeling in Virtual Reality - Yigitbas, Enes; Gorissen, Simon; Weidmann, Nils; Engels, Gregor (Software Engineering 2022, Fachtagung des GI-Fachbereichs Softwaretechnik, 21.-25. Februar 2022, Virtuell)

Search Space Characterization for Approximate Logic Synthesis - Witschen, Linus Matthias; Wiersema, Tobias; Reuter, Lucas David; Platzner, Marco (2022 59th ACM/IEEE Design Automation Conference (DAC))

MUSCAT: MUS-based Circuit Approximation Technique - Witschen, Linus Matthias; Wiersema, Tobias; Artmann, Matthias; Platzner, Marco (Design, Automation and Test in Europe (DATE))

Exact output tracking in prescribed finite time via funnel control - Lanza, Lukas Johannes
We extend a recent result in high-gain feedback output tracking control to achieve exact tracking within finite time, i.e., the output of a system and its relevant derivatives have certain exact values at a predefined finite time. We propose a new funnel control scheme achieving this, whereas the error between the reference and the output evolves within prescribed bounds. Applications of this are, for instance, linking up two parts of a train, or docking spaceships.

Weiterentwicklung der induktiven Schnellhärtung von Klebverbindungen für robuste Fertigungsprozesse unter Berücksichtigung von serienrelevanten Einflussfaktoren - Kowatz, Jannik; Teutenberg, Dominik; Meschut, Gerson (22. Kolloquium Gemeinsame Forschung in der Klebtechnik)

Analyse des Versagensverhaltens geklebter Stahl-Verbindungen beim werkstoffschonenden Entfügen in der Karosserieinstandsetzung - Chudalla, Nick; Meschut, Gerson; Bartley, Aurélie; Wibbeke, Tim Michael (22. Kolloquium: Gemeinsame Forschung in der Klebtechnik)